Niemerytoryczny profesjonalizm - o czym świadczy „martwy" Fundusz Ekspercki? - Marcin Rafałowicz (Świat Idei i Polityki, 2008)
The growing complexity of human world both on local and global level force far-reaching specialization and professionalization in political activity as well. The same time in instead of increasing essential assets of politics Poland we deal with explosion of politics' mediagenic. Polish politicians with pleasure reduce any political debate to the level of emotions appealing to simple associations and stereotypes. Expert Found was the one that have had to bring our political scene to the higher level. However, it seems that it is failed creation and political parties are not able to take advantage of founds that are transferred to such institution. It also constitutes certain temptation for political activists and their background to whom occur preparation of paid opinions having doubtful usefulness for party organizations. It seems that Expert Found could be successfully eliminated from political-legal polish system but questions regarding essentiality of our political scene might be regulated by natural social processes. Politics in democratic systems respond on particular demand and if such expectation of their electorate will be than they are forced to increase a standard of politic they pursued. It is as well optimistic conception as full of hope since in Poland there is still a need for efficient politics characterized in professionalism.